Carbon sequestration and yield performances of Miscanthus × giganteus and Miscanthus sinensis. Issue 4 (4th July 2018) - Nakajima, Toru; Yamada, Toshihiko; Anzoua, Kossonou Guillaume; Kokubo, Rin; Noborio, Kosuke
Abstract: The demand for renewable energy resources, such as Miscanthus spp., has increased significantly in temperate regions. Miscanthus spp. has the potential to mitigate GHG emissions by replacing fossil fuels and sequestering carbon in soil. However, the biomass yield and C sequestration performance of Miscanthus spp. varies by climate, soil type, management practices, and land-use history. Therefore, there is a need for site-specific research on biomass yield and C sequestration of Miscanthus × giganteus ( M × g ). An alternative to M × g is the seed-propagated Miscanthus sinensis which could be another option as a bioenergy crop. The objective of this study was to assess the C sequestration rates and biomass yield performance of these two Miscanthus spp. The C sequestration rates were measured in side-by-side comparison plots using the 13 C natural abundance technique. The results revealed C sequestration rates of M × g and M. sinensis were 1.96 ± 0.82 and 0.99 ± 0.21 Mg C ha −1 year −1 over 6 years. The average biomass yields of M × g and M. sinensis from 2010 to 2015 were 25.6 ± 0.2 and 31.2 ± 0.5 Mg ha −1 year −1, respectively. It can be concluded that M. sinensis has a higher yield while M × g has a higher potential for immediate C sequestration in cool regions such as Northern Japan.